China's personal credit reporting system in the internet finance era: challenges and opportunities. Issue 3 (1st September 2016) - Huang, Zhuo; Lei, Yang; Shen, Shihan
ABSTRACT: The credit reporting system plays an important role in a credit economy, alleviating information asymmetry and reducing transaction costs. This article reviews the historical developments and describes the current structure of China's government-oriented personal credit reporting system. The article summarizes the rapid development of Internet finance since 2013, and analyzes the challenges and opportunities for the next generation of China's personal credit reporting system.